Tears or fearsn - Domingo, Jessica; Feliciano Leilani; Lazaro, Cheche; Santos, Owen. (Quezon city Probe Productions, 1993)
Traces the political career of Ferdinand Marcos and events during his administration.
VHS
Keywords: Marcos, Ferdinand Edralin, 1917-1992.; Marcos administration